ESTUPRADA: A CULPABILIZAÇÃO DA MULHER VÍTIMA DE ESTUPRO PELA TUTELA PATRIARCAL DO SISTEMA PENAL. - CAMPOS, Danielly Thays (2021)
In the context of rape, it is not uncommon that, in addition to this violation, the victim still goes through a process of stigmatization that places her as the true culprit for the evil suffered, therefore, a research aims to investigate the patriarchy in the grounds of the tutelage offered by the Criminal Justice System in cases of rape crimes against women, silencing the victim's word and blaming her. The methodology is based on Content Analysis to support a quantitative and qualitative approach to the research. It also analyzes 30 judgments of criminal appeals related to rape criminal actions in the State of Maranhão, within the same period from 2017 to 2020 and whether to use, still, the Bibliographic and Documentary Review about the most relevant themes that permeate the central question The value of gender and patriarchy is debated as a category of analysis to characterize the characteristics of stereotyped treatment of rape victims, demonstrating the basis patriarchal of the functioning of the Brazilian Criminal Justice System that mitigates its guarantor discourse and identifying how the Judiciary resignifies this sexual violation, blaming the victim based on patriarchal stigmas hidden under the veil of legal discourse.